Analisis Faktor-faktor yang Mempengaruhi Kinerja Karyawan di Unit Customer Care dan Customer Service Relationship PT. XYZ - Novita Sianipar; Aulia Fashanah Hadining (Universitas Indraprasta PGRI Jakarta, 2023)
Employees play an important role in running a company's operation. Their performance can determine whether or not a company can operate efficiently. There are a number of aspects that can affect employee performance in a company, two of which are QualityiofiWorkiLife and Job Satisfaction. This research is aimed at examining the effect of Quality of Work Life and Job Satisfaction on employee performance at PT. XYZ. The sample is obtained using purposive sampling method, in which all members of the employees in the Customer Care and Customer Service Unit of PT. XYZ participate as respondents, with a total of 10 respondents. The method used in data processing is Multiple Regression test. The t-test result for the QualityiofiWorkiLife (X1) variable is 2,948 and for the Employee Performance (Y) variable is 2,821, which is greater (>) than the t-table value of 2,365. Meanwhile, the calculated f-test result is 133,763, which is greater (>) than the F-table value of 4,46. This indicates that there is an influence between Qualityi ofiWorkiLife and Job Satisfaction on Employee Performance at PT. XYZ, both partially and simultaneously